Understanding disability policies - Drake, Robert F. (London : Macmillan, 1999)
The meaning of disability and the creation of policy. Disability policy, models and development. Policy outcomes and disabled people's responses.
Keywords: Great Britain; Handicapped; Government policy; Disability; Handicapped -- Government policy -- Great Britain; Disability -- Moral and ethical aspects -- Great Britain